Patients' requests for radiological imaging: A qualitative study on general practitioners' perspectives - Lizzie De Silva; Melissa Baysari; Melanie Keep; Peter Kench; Jillian Clarke (Wiley, 2023)
Abstract Background With the increasing availability of information, patients are becoming more informed about radiology procedures and requesting imaging studies. This qualitative study aims to explore factors that influence general practitioners' (GPs) decisions to fulfil patient requests for imaging studies during clinical consultation. Methods Semi‐structured interviews were conducted with 10 GPs working across five private medical centres in Northwest Sydney. Conventional content analysis was used with emergent themes to identify GPs perspectives. Results Six themes stood out from the interviews with GPs fulfilling patient requests for imaging studies. They included four pertaining to patient factors: patient expectations, 'therapeutic scans', 'impressive labels' and entitled. Two further themes pertained to the GP perspective and included defensive medicine, and 'new patients'. Requests are fulfilled from anxious or health‐obsessed patients, with GPs worrying about litigation if they refuse. However, GPs decline requests from patients with entitlement attitudes or during first visits. Discussion The findings suggest that GPs struggle to balance their responsibilities as gatekeepers of imaging with patients' expectations of request fulfilment. Clear guidelines on the appropriate use of diagnostic imaging and its limitations could help patients understand its proper use and ease anxiety. Additionally, education and training for GPs could help them manage patient expectations and provide appropriate care. Patient Contributions Patients, service users, caregivers, people with lived experiences or members of the public were not directly involved in the design, conduct, analysis or interpretation of the study. However, our study was conducted in primary care facilities where the GPs were interviewed about patients' requests for diagnostic imaging based on their own initiatives. GPs' perspectives in managing patient expectations and healthcare utilisation were explored within the Australian Medicare system, where medical imaging and image‐guided procedures come at little to no cost to the individual. The study findings contribute to a better understanding of the challenges faced by GPs in dealing with patient consumerism and requests for diagnostic imaging, as well as factors influencing request fulfilment or denial. Insights gained from this study may inform future research about delivering patient‐centred care within a similar context.